KONSTRUKSI MAKNA ISTILAH DALAM GARAP REBAB SUNDA - Sopandi, Caca (LP2M ISBI Bandung, 2017)
The terms applied in working on playing the rebab in Sunda certainly appear after the musical form. In fact, the terms also mostly use terms that are considered to be the closest to reality both audio and visual. However, there are a number of other terms which are based more on things outside of reality, so that the construction of the meaning of these terms contains messages far beyond the technique. The problems in this study are: (1) What are the meaning constructions that underlie the creation of terms in the Sundanese rebab work? (2) What is the correlation between the terms that are built with the form of Sundanese rebab musicality? The purpose of this study is to find out, understand and explain: (1) the construction of the meaning of terms in the Sundanese rebab, (2) the correlation of terms with their musicality. Data collection techniques used were participant observation, interview and documentation study. Data analysis is carried out by identifying, reducing, clarifying, describing, interpreting and concluding all information selectively. The results of the research show that: (1) the terms used in the rebab play are two categories of terms, including terms with denotative conceptual meanings, and terms with connotative meaning concepts, (2) The technique of playing the rebab requires accuracy, precision, and interpretation. Therefore these terms are used as methods and strategies in the process ofinheritance.